The evolution of the doctor/patient relationship: yesterday, today, and tomorrow - von Engelhardt, Dietrich (Medicina e Morale, 1999)
This article deals with the evolution of doctor patient relationship with respect to different historical periods: the Ancient Times, the Middle Ages, the Modern Age. The author underlines how important the History of Medicine is in preventing the technological shift of doctor/patient relationship and in enriching this relationship with the anthropological, cosmological, and metaphysical dimension. In order to follow this path, the Author suggests to use some artistic representations, since artistic works do have therapeutic force: "human culture and medicine are deeply interwound. Any artistic form may be useful to diagnostics, therapy, prevention, and rehabilitation; it may also offer various help strategies concerning the attitude towards sickness, pain, and death". Doctor/patient relationship does not depend on medicine only, but is also the expression of culture and society, to which medicine itself belongs. Because medicine is not outside society - though it has its own autonomous mechanism - it is necessary to take the cultural context into consideration in order to contribute to the humanisation of medicine and assistance. The Author highlights that the aim of the future medicine must be the recovering of a connection among anthropology, cosmology, metaphysics and science. In fact, there must be no separation between an experimental - "scientific" medicine and a medicine based on anthropology, cosmology, and metaphysics. For this reason, doctor patient relationship is the central issue that can accomplish the gathering of natural science and humanities.